Monetary policy after the Great Moderation - Guillermo Pe\~na (Journal of Central Banking Theory and Practice, 2020)
The interferences among some financial, economic and monetary variables are checked as an indicator of economic performance in the long run and for the monetary policy applied between the Great Moderation (GM) of 1987-2001 and the Global Financial Crisis of 2007-2009. For achieving this target, some Granger causality tests are applied to GDP growth, credit growth, and lending interest of 36 countries of the EU and the OECD for the full sample of 1987-2012 and the sub-sample of 2002-2007. Results corroborate the interferences among these variables for the discretionary monetary policy applied immediately after the GM, within the "Ad Hoc Era" or "lax period", and independence when monetary policy was correctly applied and rules-based.
Keywords: E43; E50; 330; Monetary policy; Economic growth; Financial crises; Great Moderation; Central Banking